2020
DOI: 10.3390/ijerph17051566
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of LED Color Rendering on the Dark Adaptation of Human Eyes at Tunnel Entrances

Abstract: The dark adaptation of drivers’ eyes at a tunnel entrance seriously affects traffic safety. This can be improved by the design of tunnel lighting. Light-Emitting Diode (LEDs) have been applied as a new type of luminaire in tunnel lighting in recent years, but at present, there are few studies on the influence of color rendering of LEDs on tunnel traffic safety, and there is no explicit indicator for the selection of appropriate color rendering parameters in tunnel lighting specifications, which has aroused res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In its nature, a freeway tunnel possesses traffic hazards given its constraint driving space and tedious driving environment [ 48 , 49 ]. Poor lighting and fatigued driving in a tunnel are also often considered as potential hazards causing crashes, especially severe ones [ 50 , 51 ]. Based on the definition, a secondary CC happens very shortly after the primary crash occurs, meaning that there is extremely limited time for the following drivers to react to the primary crash.…”
Section: Discussionmentioning
confidence: 99%
“…In its nature, a freeway tunnel possesses traffic hazards given its constraint driving space and tedious driving environment [ 48 , 49 ]. Poor lighting and fatigued driving in a tunnel are also often considered as potential hazards causing crashes, especially severe ones [ 50 , 51 ]. Based on the definition, a secondary CC happens very shortly after the primary crash occurs, meaning that there is extremely limited time for the following drivers to react to the primary crash.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that the optimum dark adaptation position of the driver of a large truck is closer to the door, and there is a higher visual load when driving along a tunnel entrance section, resulting in poor driving safety [16][17][18][19]. Zhaoet al analyzed the influence of light-emitting diode (LED) color rendering on the dark adaptation of the human eye at a tunnel entrance [20]. Dong et al [21] revealed that LEDs with correlated color temperatures (CCTs) ranging from 4000 to 4500 K are preferable for tunnel entrance lighting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely important to study the traffic safety of urban tunnels. However, existing tunnel traffic safety research mainly focuses on expressway tunnels, and the research related to the traffic safety of urban tunnels is relatively scarce, but whether expressway tunnel traffic safety-related research conclusions are applicable to urban tunnels still needs to be further verified [8][9][10]. At present, the traffic capacity of the entrance and exit sections of urban tunnels is low, and the phenomenon of drivers changing lanes at will to overtake is serious.…”
Section: Introductionmentioning
confidence: 99%